1998
DOI: 10.1021/jf9801264
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Flavonoids from Artemisia vulgaris L.

Abstract: The comprehensive quantitative analysis of the flavonoid chemistry of Artemisia vulgaris L., a plant used as an emmenagogue in traditional medicine, is presented in conjunction with an evaluation of its estrogenic activity. Twenty known flavonoids were isolated and identified as tricine, jaceosidine, eupafolin, chrysoeriol, diosmetin, homoeriodictyol, isorhamnetin, apigenin, eriodictyol, luteolin, luteolin 7-glucoside, kaempferol 3-glucoside, kaempferol 7-glucoside, kaempferol 3-rhamnoside, kaempferol 3-rutino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 13 publications
(17 reference statements)
3
45
0
1
Order By: Relevance
“…The phytochemical studies on this plant species reported that it contains a number of flavonoids (e.g., apigenin, eriodictyol, kaempferol, luteolin) as the major constituents, together with monoterpenes, sesquiterpene lactones, and other compounds. [18][19][20] Flavonoids are well known antioxidants and attract a tremendous amount of interest among researchers as possible therapeutic agents for diseases mediated by free radicals. Flavonoids are also effective inhibitors of several enzymes including XO, cyclooxygenase, and lipooxigenase.…”
Section: Resultsmentioning
confidence: 99%
“…The phytochemical studies on this plant species reported that it contains a number of flavonoids (e.g., apigenin, eriodictyol, kaempferol, luteolin) as the major constituents, together with monoterpenes, sesquiterpene lactones, and other compounds. [18][19][20] Flavonoids are well known antioxidants and attract a tremendous amount of interest among researchers as possible therapeutic agents for diseases mediated by free radicals. Flavonoids are also effective inhibitors of several enzymes including XO, cyclooxygenase, and lipooxigenase.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogenic flavonoids [62]. Jaceosidine, eupafolin, luteolin, quercetin, apigenine, aesculetin, esculetin-6-methylether, and scopoletin [63].…”
mentioning
confidence: 99%
“…Its extracts are recommended to women for a wide variety of gynecological problems (Chevallier 1996;OnHealth.com 2000). The most common homeopathic use of A. vulgaris is for the treatment of irregular menstruation and relief of menopausal ailments (Phillips and Foy 1990;Lee et al 1998). Different parts of A. vulgaris are also used for a multitude of other medicinal purposes including as antibacterial, anti-inflammatory, antiseptic, diaphoretic, emmenagogic, or stimulatory agents (Miller 2000).…”
Section: Namementioning
confidence: 99%